Digital Citizenship in the National and Civic Education ‎Textbooks: Analytical Study.‎ - Tawalbeh, Hadi (Jordan Journal of Educational Sciences, 2017)
The study aimed to identify the degree of embedding digital citizenship concepts in the national and civic education textbooks, and the familiarity of the teachers of digital citizenship concepts. The sample of the study consisted of 43 teachers of the national and civic education textbooks in Irbid governorate, and all the textbooks of national and civic education for the academic year 2016/2017. The Researcher adopted structured interviews and content analysis of all collected surveyed data. The results revealed an absence of the use of the term digital citizenship in all the national and civic textbooks and they were free of any recurrence of 63 concepts. The results also revealed that of 56 concepts, 36 of them appeared in the textbook of national education of eighth-grade alone, and as the number of occurrences of 33 concepts were 3 or less. The digital access and digital literacy were the axes which their concepts were included in all the textbooks of national and civic education, and five of the nine axes only appeared in the textbook of national and civic education of eighth-grade. The results revealed the absence of the knowledge of the teachers of national and civic education of the axes and concepts of digital citizenship.